The assessment of twin pregnancies delivered in our clinic: three-year experience - Şanlı, Cengiz; Kavak, Salih Burçin; Aslan, Melike; Çelik Kavak, Ebru; Batmaz, İbrahim; Bulu, Gülay (Perinatal Medicine Foundation, 2020)
Objective: Twin pregnancies constitute 1-2% of all pregnancies. With the recent developments in assisted reproductive technologies, the incidence of multiple pregnancy has increased. Preterm labor is held responsible for the poor neonatal outcomes primarily. In our study, we aimed to assess fetal-maternal outcomes of twin pregnancies seen in our clinic. Methods: One hundred and thirty twin pregnancy cases out of 4241 pregnant women who delivered in our clinic between 01.01.2017 and 01.01.2020 were included in the study. The labor records of the patients were reviewed retrospectively and their data for age, week of gestation, delivery type, birth weight, fetal sex, chorionicity characteristics and laboratory parameters were recorded. Definitive statistics and SPSS 21.0 for statistical analyses were used to evaluate the data obtained from the study. The data were presented as mean ± SD (standard deviation). Results: The incidence of twin pregnancy was found 3%. In the ultrasonographic imaging evaluated during diagnosis, 27.7% of the cases were monochorionic and 72% of them were dichorionic. Of the pregnant women, 12.3% were at term and 87.7% were at preterm period. When the preterm fetuses were evaluated, 37.7% of 114 preterm fetuses were delivered at late preterm period, 29.2% of them at mid-preterm period and 20.8% at premature preterm period. The rates of treatment pregnancy (pregnancy provided by ovulation induction and assisted reproductive technologies) and spontaneous twin pregnancy were 20% and 80%, respectively. Mean maternal age was found 31.3. When evaluated in terms of maternal morbidity, preterm labor and premature rupture of membrane were the most common problems. Mean newborn weight was 1832g and 59.3% of the newborns had low birth weight and 21.8% of them had very low birth weight. While one fetus had transverse presentation in 12.5% of the patients, at least one fetus had breech presentation in 53.1% of the cases and 34.4% of the cases had head-head presentation. Conclusion: Twin pregnancies are characterized by the increased feto-maternal risks. Therefore, both antenatal and intrapartum management should be maintained diligently.